Study Literature Riview : Hambatan Voluntary Counseling And Testing (VCT) Pada Ibu Hamil - Yunri merida; Fatya Nurul Hanifa (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Background: According to (Ghoma-Linguissi et al., 2015a) there are several factors that influence HIV counseling and testing, including motivation, awareness and education. Meanwhile, according to (Kunkel et al., 2017) the factors that influence HIV counseling and testing are the factors of patients and midwives in providing counseling. Objective: This literature study aims to determine the barriers to Voluntary Counseling and Testing (VCT) in pregnant women. Method: The method used for writing this research is to use a systematic literature review. Search articles using the PubMed database, Google Scholar, and Approach. The article selection process uses PRISMA flow and diagrams. Results: The results obtained are the need to increase promotion and preventive education in an effort to provide information about barriers to voluntary counseling and testing (VCT). Suggestions need to be increased training for counselors with standard curriculum and refresher courses, for HIV counseling and testing, specifically for health workers.